Oxidative stress and its impact on skin, scalp and hair - Trüeb, Ralph M. (International journal of cosmetic science, 2021)
Oxidative stress is an unbalanced condition in which the tissues of the body are not sufficiently able to counteract either exogenous or endogenous sources of reactive oxygen species. Oxidative stress is strongly associated with ageing, both local and systemic, as well as a wide range of local health conditions. This review focuses on the oxidative stress data known for skin, scalp and hair. This oxidative stress may be the ‘currency’ by which an unhealthy scalp leads to deleterious consequences to the hair. The ramifications of this scalp oxidative stress to normal hair elongation, retention and replacement are discussed. Résumé Le stress oxydatif est une condition déséquilibrée dans laquelle les tissus du corps ne sont pas suffisamment capables de contrer la source exogène ou endogène d’espèces réactives de l’oxygène. Le stress oxydatif est fortement associé au vieillissement, à la fois local et systémique, ainsi qu’à un large éventail de problèmes de santé locaux. Cette revue se concentre sur les données de stress oxydatif connues pour la peau, le cuir chevelu et les cheveux. Ce stress oxydatif peut être la « devise » par laquelle un cuir chevelu malsain entraîne des conséquences délétères pour les cheveux. Les ramifications de ce stress oxydatif du cuir chevelu sur l’allongement, la rétention et le remplacement normaux des cheveux sont discutées.